The Arab spring, good governance and citizens' right - Akhmetova, Elmira (International Institute of Advanced Islamic Studies Malaysia (IAIS), 2014)
This article is a study of the origins and consequences of the Arab Spring through highlighting the higher objectives of the Shariah in governance, as well as the basic rights and responsibilities of the citizens and the rulers in Islam. The paper suggests that maintaining peace, harmony and social stability are the main objectives of Islam in governance. But revolutionary changes commonly destroy social harmony and well-being; and produce chaos, insecurity, injustice and economic collapse. At the same time, the citizens own rights to disobey their deviant rulers. Accordingly, through discussing the rights and responsibilities of the citizens before their rulers and of the rulers before their people, the paper recommends adoption of the approach of nonviolent and evolutionary changes to improve political and social ills. It also suggests that governments should conduct peaceful, fair-minded and just rule rather than giving people no other option but to create public havoc. The paper also suggests that Islamic principles in governance, as embedded in the text and traditions, are conducive to good governance and democratic thought in many compelling ways.